2012
DOI: 10.1590/s1519-99402012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Produção de forragem de Tifton 85 adubado com nitrogênio e submetido à lotação contínua

Abstract: O presente estudo foi realizado na Unidade de Pesquisa e Desenvolvimento de Adamantina/SP, da Agência Paulista de Tecnologia dos Agronegócios (APTA) - Pólo da Alta Paulista, com o objetivo de avaliar o efeito da adubação nitrogenada na composição morfológica, densidade populacional de perfilhos, índice de área foliar, interceptação luminosa e acúmulo de forragem em pastos de Tifton 85 submetidos ao regime de lotação contínua. Os tratamentos corresponderam a quatro doses de Nitrogênio (0; 100; 200 e 400kg/ha/an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
17

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
1
5
0
17
Order By: Relevance
“…NOGUEIRA et al, 2013;TEIXEIRA et al, 2013;QUEIROZ et al, 2012;OLIVEIRA et al, 2011;FONSECA et al, 2007). The non-irrigated productivity is compatible with the averages found from 55 to 83 kg ha -1 day -1 (FAGUNDES et al, 2012;AGUIAR et al, 2010). in the summer, observed linear increases in productivity of Tifton 85 grass, where the accumulation of dry mass was between 21.2 to 107.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…NOGUEIRA et al, 2013;TEIXEIRA et al, 2013;QUEIROZ et al, 2012;OLIVEIRA et al, 2011;FONSECA et al, 2007). The non-irrigated productivity is compatible with the averages found from 55 to 83 kg ha -1 day -1 (FAGUNDES et al, 2012;AGUIAR et al, 2010). in the summer, observed linear increases in productivity of Tifton 85 grass, where the accumulation of dry mass was between 21.2 to 107.…”
Section: Resultssupporting
confidence: 86%
“…The irrigated LSR was higher than the non-irrigated (Table 5), as well as for SANCHES et al (2015) working with Tifton overseeding with oats found average values of 2.8 and 1.8 with and non-irrigated, respectively. The DeM depending on the doses showed a slight linear decrease (Y = 7.51 -0.035 * N), as well as in a study conducted in Adamantina-SP, with Tifton 85, in which percentage of DeM decreases from 17 to 7% from the highest to the lowest dose of nitrogen (FAGUNDES et al, 2012). Thus, according to MARENCO & LOPES (2009), leaf senescence is a symptom of nitrogen deficiency for the plant.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Esses dados estão de acordo com o que afirmam Costa et al (2008) O aumento no teor de MM observado nas forrageiras não irrigadas demonstra que o estresse hídrico leva a morte dos tecidos, diminuindo a qualidade nutricional da planta. Segundo Fagundes et al (2012), as variações nos Oliveira et al (2015) Archives O menor teor de NT no nível irrigado em comparação ao não irrigado, observado nas forrageiras do presente trabalho, pode ser devido ao maior crescimento que essas espécies apresentaram quando submetidas à irrigação e com o aumento no percentual de colmo (Tabela 1), como citado por Cunha (2007).…”
Section: Resultsunclassified